The Importance of Phonological Awareness in Learning Disabilities’ Prevention: Perspectives of Pre-School and Primary Teachers - Veríssimo, Lurdes; Costa, Marisa; Miranda, Francisca; Pontes, Catarina; Castro, Isabel (Frontiers in Education, 2021)
There is robust empirical evidence regarding predictors of success in reading and writing. However, pre-school and primary teachers are not always aware of this evidence and often do not know how to apply it in practice. Considering the importance of the role of these teachers and the importance of early school years in preventing learning difficulties, it is essential to study teachers´ attitudes, knowledge, and strategies for improving educational processes toward successful development of literacy skills. Particularly, recognizing the impact of phonological awareness on the development of reading skills, this study has two main research questions: What is the importance pre-school and primary teachers attribute to the promotion of phonological awareness? and Which strategies for promoting phonological awareness do they apply in their professional practice? This qualitative study includes interviews with 10 pre-school and primary teachers, seeking to understand the perspective of each participant about phonological awareness, its importance and implementation in practice. Data were collected in a context of great adversity (e.g., child maltreatment, early life stress). The results reveal that both pre-school and primary teachers recognized the relevance of phonological awareness among other pre-academic skills. Regarding the activities teachers implement, in their perspective, the playfulness seems to better result to stimulate this specific skill. Preschool teachers tend to focus on the dynamics that promote syllabic, intrasyllabic and phonemic awareness. Despite recognizing the gaps in phonological awareness in the first graders, primary teachers seem not to prioritize activities that stimulate and consolidate this skill, privileging the fluency and comprehension processes. The collaborative work between professionals was highlighted as very important to optimize the stimulation phonological awareness as well as facing other learning difficulties teachers in this context find. The results are discussed considering the role of pre-school teachers and primary teachers in reading difficulties’ prevention in contexts facing multiple vulnerabilities.